Adaptive terminal guidance law with impact-angle constraint. (29th November 2017) - Gao, C.; Li, J.; Feng, T.; Jing, W.
ABSTRACT: This paper proposes an adaptive guidance law for attacking a ground target based on motion camouflage strategy. The coefficients of normal and bi-normal feedback guidance law are given according to the relative motion relationship under Frenet frame. Utilizing the coefficients, the motion camouflage proportional guidance law is derived. In order to improve the initial overload characteristic of the missile, an adaptive feedback coefficient is introduced. Then, the adaptive guidance law is applied to a longitudinal plane interception problem with impact-angle constraint. Finally, the validity of this guidance law for air-to-ground missiles is proved by simulations.